Parametric optimization of polycaprolactone synthesis catalysed by Candida antarctica lipase B using response surface methodology - Pakalapati, Harshini; Arumugasamy, Senthil Kumar; Jewaratnam, Jegalakshimi; Wong, Yong Jie; Khalid, Mohammad (Wiley, 2018)
A statistical approach with D-optimal design was used to optimize the process parameters for polycaprolactone (PCL) synthesis. The variables selected were temperature (50°C-110°C), time (1-7 h), mixing speed (50-500 rpm) and monomer/solvent ratio (1:1-1:6). Molecular weight was chosen as response and was determined using matrix-assisted laser desorption/ionization time of flight (MALDI TOF). Using the D-optimal method in design of experiments, the interactions between parameters and responses were analysed and validated. The results show a good agreement with a minimum error between the actual and predicted values.